Human Resource Development Practices and Employee Performance in Private Hospitals: Evidence from Emerging Healthcare Systems - Jothi P, Manicka; Sangeeta, S.Sangeeta (Utan Kayu Publishing, 2025)
Despite extensive research on Human Resource Development (HRD), few studies have examined how socio-demographic factors influence the effectiveness of HRD practices on employee performance in private hospitals within emerging healthcare systems. This study investigates the relationship between HRD practices and employee performance at Assured Best Care Hospital, using a descriptive–correlational design with 50 participants selected through simple random sampling. Data were collected using a structured questionnaire and analyzed with SPSS. Results reveal no significant difference in performance across educational levels (p = .629) and tenure groups (p = .230), yet positive correlations were found between updated training (r = .48, p < .05), supervisor support (r = .45, p < .05), learning climate (r = .43, p < .05), and career growth opportunities (r = .41, p < .05) with employee performance. These findings support the Human Capital Theory and Social Exchange Theory by demonstrating that HRD enhances performance through capability building and reciprocal motivation. The study extends HRD scholarship by contextualizing these mechanisms within resource-constrained hospital settings. Practically, the results emphasize the need for continuous, competency-aligned training, effective coaching, and transparent career development to sustain engagement and performance. The findings inform hospital administrators about the strategic importance of HRD in achieving service excellence.